Hubungan Pengetahuan dan Sikap Ibu Hamil dengan Kunjungan Antenatal Care (ANC) di Wilayah Kerja Puskesmas Bapinang - Kresensia Kondamaru; Dwi Agustian Faruk Ibrahim; Ayu Puspita (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Knowledge is the result of knowing, which occurs after a person perceives an object. Attitude refers to views, opinions, or feelings toward a specific object, person, or event. Antenatal care (ANC) refers to pregnancy check-ups and is defined as prenatal monitoring, primarily aimed at the growth and development of the fetus in the womb. Based on field observations, the researcher found that pregnant women who rarely or do not attend ANC visits often experience complications during pregnancy, postpartum complications, babies born with low birth weight (LBW), preterm births, and pregnant women only seek healthcare services when problems arise in their pregnancy. Additionally, there are still pregnant women who deliver with the assistance of traditional birth attendants or midwives in the village. This study aims to determine the relationship between pregnant women's knowledge and attitudes with ANC visits in the working area of Bapinang Health Center. Research Methods: This study used a cross-sectional design. The instrument used was a questionnaire, and the data were analyzed using the Chi-Square statistical test, with 34 pregnant women as respondents. Results: The study found a significant relationship between pregnant women's knowledge and ANC visits with a p-value of 0.001 < 0.05, meaning that H1 is accepted. It can be concluded that there is a relationship between knowledge and ANC visits in the working area of Bapinang Health Center. Similarly, the attitude variable had a p-value of 0.004 < 0.05, so H2 is accepted. It can be concluded that there is a relationship between pregnant women's attitudes and ANC visits in the working area of Bapinang Health Center. Conclusion: This study concludes that there is a relationship between pregnant women's knowledge and attitudes with ANC visits in the working area of Bapinang Health Center.